Health Promoting Leadership in a Virtual Context - Mokoaleli, Tsepang (Organisational Psychology, 2023)
Organisational leadership is regarded as one of the most important aspects of the workplace as it has been linked to productivity and efficiency and significantly influences employee health and well-being. The outbreak of COVID-19 and the shift to virtual work has shifted job demands and often increased stress. Hence, effective leadership is required to foster work conditions that are focused on promoting the health of employees. The importance of the role of leadership in creating healthy workplaces has been well established. Health-promoting leadership is a positive leadership approach thought to be instrumental in influencing employee well-being and health outcomes indirectly by focusing on changing the working conditions of employees. The main objective of this study was to identify if health-promoting leadership is related to health and well-being (work-related well-being and emotional exhaustion) in an environment in which a rapid shift to virtual working had taken place due to the COVID-19 pandemic. The study employed a descriptive, cross-sectional and quantitative research design. Convenience sampling using a snowball approach was employed. In total, 104 employees completed an online survey. The results showed that, as expected, the seven individual dimensions of health-promoting leadership were predictors of work-related well-being but not predictors of emotional exhaustion and health complaints. Therefore, the study contributes to the literature on health-promoting leadership and showed that leaders need to particularly focus on enhancing a sense of community for virtually working employees. This is through weekly online meetings as they provide employees with a space where they can interact with each other, and also share ideas with each other.